The Influence of Dental Virtualization, Restoration Types, and Placement Angles on the Trueness and Contact Space in 3D-Printed Crowns: A Comprehensive Exploration - Tsung-Yueh Lu; Wei-Chun Lin; Tzu-Hsuan Yang; Citra Dewi Sahrir; Yung-Kang Shen; Sheng-Wei Feng (MDPI AG, 2023)
The current digital dentistry workflow has streamlined dental restoration production, but the effectiveness of digital virtual design and 3D printing for restorations still needs evaluation. This study explores the impact of model-free digital design and 3D-printing placement angles on restorations, including single crowns and long bridges produced with and without casts. The restorations are 3D printed using resin at placement angles of 0°, 60°, and 90°. Each group of samples was replicated ten times, resulting in a total of 120 restorations. The Root Mean Square Error (RMSE) value was used to evaluate the surface integrity of the restoration. In addition, the contact space, edge gap, and occlusal space of restorations produced by different processes were recorded. The results indicate that there was no significant difference in the RMSE value of the crown group (p > 0.05). Changing the bridge restoration angle from 0° to 90° resulted in RMSE values increasing by 2.02 times (without casts) and 2.39 times (with casts). Furthermore, the marginal gaps in the crown group were all less than 60 μm, indicating good adaptation. In contrast, the bridge group showed a significant increase in marginal gaps at higher placement angles (p > 0.05). Based on the findings, virtual fabrication without casts does not compromise the accuracy of dental restorations. When the position of the long bridge exceeds 60 degrees, the error will increase. Therefore, designs without casts and parallel placement result in higher accuracy for dental restorations.